Posture, Muscle Activity and Oxygen Consumption Evaluations Among Metal Stamping Operators: A Pilot Study in Malaysian Small and Medium Industries - Isa, Halim (The Institution of Engineers, Malaysia, 2011)
In the new era of world industrialization, ergonomics plays an important role to improve occupational health and productivity in most industries including small and medium industries (SMIs). However, SMIs in Malaysia do not put any priority on ergonomics awareness, for an example, by not designing the workstation ergonomically. As a consequence, operators are exposed to various ergonomic risk factors and prone to have ergonomic injuries. The objectives of this study are to evaluate working posture, muscle activity, and oxygen consumption while operators perform metal stamping process in a workstation, before and after the workstation is modified. The Rapid Entire Body Assessment (REBA), surface electromyography (SEMG), and oxygen analyzer are used to evaluate working posture, muscle activity, and oxygen consumption respectively. Results of evaluations found that the modified workstation has reduced the physiological stress such as extreme posture, work/loading in the muscles as well as energy expenditure. The study concluded that an ergonomic workstation design can contribute significantly to improve physiological performance of the operators.